2008
DOI: 10.1177/1470320308097499
|View full text |Cite
|
Sign up to set email alerts
|

Association of insertion/deletion polymorphism of angiotensin-converting enzyme gene with essential hypertension and type 2 diabetes mellitus in Malaysian subjects

Abstract: The D allele of the ACE gene is associated with essential HTN and T2DM in Malaysian subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 25 publications
4
43
1
Order By: Relevance
“…The frequency of this genotype among hypertensives in the current study (17.18%) was higher than that found for Malaysian and Bangladeshi individuals (10.76% and 11.40%, respectively); however, a Chinese population had a lower frequency. [27][28][29] The insertion and deletion alleles were significantly related to hypertension in the current study, which correlates with the findings of a similar North Indian study. 15 A positive correlation has been reported between various obesity variables like BMI and WHR, including oxidative stress markers such as reduced erythrocyte glutathione.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of this genotype among hypertensives in the current study (17.18%) was higher than that found for Malaysian and Bangladeshi individuals (10.76% and 11.40%, respectively); however, a Chinese population had a lower frequency. [27][28][29] The insertion and deletion alleles were significantly related to hypertension in the current study, which correlates with the findings of a similar North Indian study. 15 A positive correlation has been reported between various obesity variables like BMI and WHR, including oxidative stress markers such as reduced erythrocyte glutathione.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to traditional life-style risk factors, genetic background may also be pivotal in the pathogenesis of type 2 DM (T2DM) and HTN with the important and complex involvement of the renin angiotensin aldosterone system (RAAS) (3).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Several studies in different populations have found that ACE I/D polymorphisms are strongly associated with hypertension, which is a known risk factor for IA. [41][42][43][44] ACE I/D polymorphisms have also been extensively studied in several cardiovascular adult diseases, such as thoracic aortic dissection, 45 ischaemic stroke, 13 coronary heart disease, 14,46 left ventricular hypertrophy 47 and intracerebral haemorrhage. [15][16][17][18][19][20] In conclusion, data from the present study suggest that the ACE DD genotype may be a protective factor against IA in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%